Effects of Taurine as Dietary Supplement on the Biological and Demographic Parameters of Nezara viridula (Heteroptera: Pentatomidae). Issue 1 (2nd February 2023) - Rojas, M Guadalupe; Morales-Ramos, Juan A
Abstract: The southern green stink bug, Nezara viridula (L.) (Heteroptera: Pentatomidae), is a widely distributed pest of many economically important crops. Because of its economic impact, multiple examples of rearing methods and diets for N. viridula have been published. However, rearing this pest year-round consistently in all-vegetable diets has been challenging. Preliminary observations have shown that supplementing N. viridula diet with insect components improves the survival and reproduction of this insect. We hypothesized that taurine could be the nutrient present in insect components that was providing the benefits. Treatments consisting of three different watering regimes: 1) Reverse osmosis (RO) water only (W), 2) 2% taurine solution only (T), and 3) a choice between RO water and 2% taurine solution (T&W) were compared for their effects on life cycle and demographic parameters of N. viridula . Both taurine-containing treatments (T and T&W) resulted in a significant increase in nymphal and premating adult survival and egg viability as compared with treatment 'W'. Taurine supplementation did not have significant effect on fecundity and development time significantly increased in the 'T' treatment compared with W and W&T treatments. However, there were significant improvements in demographic parameters showing an increase in fitness levels after taurine supplementation. These results suggest that taurine is an important nutrient for N. viridula, which has been deficient in traditional diets consisting exclusively of vegetable components. Adoption of this new information will help to improve the survival of N. viridula in culture to facilitate this study to develop new methods for its control.